Peningkatan Intake Cairan Oral Pada Anak Penderita Trombositopenia Melalui Penggunaan Botol Ceria - Siti Lestari; Laura Khattrine Noviyanti; Sri Hartini MA (Lembaga Pengembangan Kinerja Dosen, 2024)
Children aged 2-5 years who suffer from thrombocytopenia are at risk of reducing oral fluid intake. Platelets are blood cells that play a role in stopping bleeding from damaged blood vessels. Bleeding increases the risk of hypovolemia. An intervention that can be used to increase oral fluid intake in children with symptoms of thrombocytopenia is giving them water using a cheerful bottle. Cheerful bottles are drinking bottles that are attractively designed, shaped like cartoon characters, and have colors according to children's favorites. When the child sucks on the bottle, a fountain will appear at the top of the bottle, thereby increasing the child's interest in drinking. This research design uses a one-group pre and post-test design. Sampling was carried out using a total sampling technique, as many as 36 respondents participated in this research. Data was collected using pre- and post-intervention oral fluid intake observation sheets. The significance value of the research results is 0.02 (P-value > 0.05), which means that there is an influence of using a cheerful bottle on increasing oral fluid intake in children with thrombocytopenia.